Gastropod Density and Diversity in the Intertidal Zone of Malalayang Beach, Manado - Sheyrel Tongkeles; Fransine B. Manginsela; Jety K. Rangan; Alex D. Kambey (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2021)
This study held in Malalayang Beach Manado, aims to determine  the density and diversity of Gastropods on the Malalayang coast of Manado. So the research objective is to find out the density and diversity of  Gastropods in Malalayang Beach, Manado. The study using the line transect technique with 50 cm x 50 cm sized. The transect line is placed perpendicular to the coastline. The distance between the line transects is 20 meters. On each transect line 5 squares are placed. The distance between squares is determined using random numbers. Gastropod species found in Malalayang Beach Manado consist of  31 species and 17 genus, each consisting of the Archaeogastropoda that consists of 3 species, Mesogastropoda consists of  9 species, and the Order of the Neogastropoda of 19 species. The total density of Gastropods in Malalayang Beach in Manado is 6.27 individuals / m2 with diversity of 3.07, according to the criteria for diversity index of Malalayang coast having high diversity. Based on this, it is suggested that Manado Malalayang Beach can be maintained and carried out management that considers the feasibility of the environment as one of the requirements for sustainable development.Keywords: Gastropods, Density, Species DiversityABSTRAK Penelitian ini dilakukan di Pantai Malalayang Manado,berkaitan dengan permasalahan yang dikemukakan bagaimanakah kepadatan dan keanekaragaman Gastropoda di pantai Malalayang Manado. Maka tujuan penelitian adalah Mengetahui kepadatan dan keanekaragaman Gastropoda di Pantai Malalayang Manado. Pengumpulan data dengan pendekatan Teknik line transect menggunakan kuadrat berukuran 50cm x 50cm. Line transect diletakkan tegak lurus dengan garis pantai. Jarak antara line transect sebesar 20 meter. Pada masing- masing line transect diletakkan 5 kuadrat. Jarak antar kuadrat ditentukan dengan menggunakan angka acak. Spesies Gastropoda yang ditemukan di Pantai Malalayang Manado terdiri dari 31 spesies dan 17 genera yang masing-masing terdiri dari Ordo Archaeogastropoda 3 spesies, Ordo Mesogastropoda 9 spesies, dan Ordo Neogastropoda 19 spesies. Kepadatan total Gastropoda di Pantai Malalayang Manado 6.27 individu/m2 dengan keanekaragaman 3,07, Menurut kriteria indeks keanekaragaman pantai Malalayang memiliki keanekaragaman yang tinggi. Berdasarkan hal tersebut, maka disarankan agar Pantai Malalayang Manado dapat dijaga dan dilakukan pengelolaan yang mempertimbangkan sskelayakan lingkungan sebagai salah satu syarat pembangunan berkelanjutan.Kata kunci: Gastropoda, Kepadatan, Keanekaragaman Jenis